From Islamic input in Medical Program to Islamic medical practice: the journey from Kulliyyah of Medicine to IIUM Medical Centre - Mohd Yusof, Nazri; Ariffin, Muhammad Irwan (Kuliyyah of Medicine, IIUM, 2020)
The journey to develop Islamic medical practice was started in Kulliyyah of Medicine, International Islamic University of Malaysia (IIUM) in 1997 with the Islamic input in Medicine Program (IIMP). The program has mature from series of lectures to a more interactive and practical teaching method over the last 2 decades. The program was later extended to the clinical post graduate clinical students in the form of discussion of its application in medical practice. The establishment of IIUM Medical Centre (IIUM MC) gives the opportunity for IIUM to practice what it’s have thought in the classroom in the real environment. This article discuss the possible methods how IIMP can be practice in IIUM MC.